PHONOLOGICAL OBJECTIVES OF THREE YEAR OLD CHILDREN - Basuki Rachmat Sinaga (Universitas Ahmad Dahlan, 2018)
This research aimed to describe language acquisition in the phonology. The method of the research was a qualitative descriptive by observation and technique of noting. The data source of the research was a record of voice of a three year four month year old child named Wesly when singing two songs of children movie shows of